Repression and Detention against Incarnation of other sexualities in The Perks of Being a Wallflower (Sudurpaschim Spectrum, 2026)
This article examines Chbosky’s The Perks of Being a Wallflower as a narrative that highlights the importance of identity recognition and the psychological consequences of social neglect, with a specific focus on how silence around sexuality shapes adolescent development. While the novel has been widely discussed for its coming-of-age themes, there is a gap in scholarly attention to the intersections of sexual repression, trauma, and identity formation through the frameworks of Lacanian psychoanalysis and Foucault’s theories of sexuality and power. The objective of this study is to analyze the protagonist Charlie’s emotional and sexual development in the context of social censorship, trauma, and institutional silence. Using qualitative textual analysis, the paper applies Lacan’s concept of the unconscious and symbolic order, alongside Foucault’s discourse on the history of sexuality and madness, to explore how Charlie’s past—marked by sexual abuse, loss, and emotional alienation. The findings suggest that the repression of dialogue around sex and trauma not only isolates individuals but also delays self-understanding and healing. The study recommends fostering open, inclusive conversations about identity and sexuality in educational and familial settings, and encourages further literary analysis of adolescent trauma using psychoanalytic and Foucauldian frameworks.